Execution of fiduciary guarantee in Sharia Banking after the court's decision number 18/PUU-XVII/2019 - Sherhan Sherhan; Pagar Pagar; Mustapa Khamal Rokan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
Execution of a fiduciary guarantee is a transfer of control of an object of collateral based on agreed terms as a return of the loan value. Based on Law Number 42 of 1999, Islamic banks as holders of fiduciary guarantee certificates have the right to execute the actions of debtors who have breached their promises through the implementation of executive titles, auction sales and underhand sales. Constitutional Court Decision No. 18/2019 had a positive impact on various interested parties directly and indirectly. Thus creating a fair legal relationship between the creditor (fiduciary recipient) and the debtor (fiduciary giver). Execution conflicts over fiduciary guarantees arise due to debtors objecting to executions carried out without prior agreement, either in the form of notification or decision from the court. This research is juridical normative with a discussion of the conditions when the executive title cannot be carried out directly unless there is a decision on execution from the court. The results of this study indicate that the Constitutional Court Decision No. 18/2019 provides a new interpretation of several phrases in Article 15 and their explanations in the Fiduciary Law. The fiduciary recipient can execute if there is an agreement with the debtor.